The effect of family control, firm size, firm growth on banking firm value - Monica Tyas Wedhari; Freddy Koeswoyo (Proceeding International Conference on Accounting and Finance, 2023)
This study aims to empirically examine the effect of family control, firm size, and firm growth on firm value. This research is in explanatory form. The sample used is a banking sector firm listed on the IDX using a purposive sampling technique. The banking sector, especially private banking, has a large family control and tends to take smaller risks because it is passed down from generation to generation to maintain the long-term viability of the firm. The criteria used are as follows 1.) banking sector companies listed on the IDX for the 2017-2022 period. 2.) companies that publish complete reports for the period 2017-2022. The results of this study indicate that the family control variable has a significant positive effect on firm value. The family control variable is the differentiating variable in this study (Holly et all, 2022) by measuring the percentage of family ownership. Firm size variable has a significant positive effect on firm value. The firm growth variable has a significant negative effect on firm value.